Connections with nature for people living with dementia. Issue 3 (29th August 2019) - Evans, Simon Chester; Barrett, Julie; Mapes, Neil; Hennell, June; Atkinson, Teresa; Bray, Jennifer; Garabedian, Claire; Russell, Chris
Abstract : Purpose: The benefits of "green dementia care", whereby people living with dementia are supported to connect with nature, are increasingly being recognised. Evidence suggests that these benefits span physical, emotional and social spheres and can make a significant contribution towards quality of life. However, care settings often present specific challenges to promoting such connections due to a range of factors including risk-averse cultures and environmental limitations. The purpose of this paper is to report on a project that aims to explore the opportunities, benefits, barriers and enablers to interaction with nature for people living with dementia in residential care and extra care housing schemes in the UK. Design/methodology/approach: Data were gathered from 144 responses to an online survey by managers/staff of extra care housing schemes and care homes in the UK. In depth-case studies were carried out at three care homes and three extra care housing schemes, involving interviews with residents, staff and family carers. Findings: A wide variety of nature-based activities were reported, both outdoor and indoor. Positive benefits reported included improved mood, higher levels of social interaction and increased motivation for residents, and greater job satisfaction for staff. The design and layout of indoor and outdoor spaces is key, in addition to staff who feel enabled to promote connections with nature. Research limitations/implications: This paper is based on a relatively small research project in which the participants were self-selecting and therefore not necessarily representative. Practical implications: The paper makes some key recommendations for good practice in green dementia care in extra care housing and care homes. Social implications: Outdoor activities can promote social interaction for people living with dementia in care settings. The authors' findings are relevant to the recent policy focus on social prescribing. Originality/value: The paper makes some key recommendations for good practice in green dementia care in extra care housing and care homes.